FIKISMART: Website-Based Learning Media for Islamic Religious Education Subjects, Topic of Fiqh for Middle Schools - Zulfa, Laila Ngindana; Azhari, Ni'am; Irvan Fuadi, Salis; Lestari, Prawidya; Khoirul Ulumuddin, Imam (Universitas Islam Negeri Raden Intan Lampung, 2025)
In the increasingly advanced digital era, the use of information technology-based learning media is very relevant and important. Given the gap between students' needs for interactive and innovative learning media and teaching methods that still tend to be conventional in Islamic Education (PAI) subjects. This study aims to examine the feasibility of developing Islamic Religious Education (PAI) learning media based on the website